2018
DOI: 10.3846/16111699.2017.1413009
|View full text |Cite
|
Sign up to set email alerts
|

Education and Gender-Based Differences in Employee Motivation

Abstract: Abstract. The main purpose of this article is to show dependencies between education and gender based on selected motivation factors. In order to obtain relevant data, the questionnaire method was used. In the years 2013-2016, 26,416 respondents participated. Descriptive statistics was used for data processing; the relationship between two categorical variables was verified by the chi-quadrate test and Tukey's HSD test. The results of the research proved the hypotheses; i.e. that there are significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 23 publications
5
41
3
1
Order By: Relevance
“…Firstly, by using the Social exchange theory, this study provides a better understanding of GHRM application and it extends the existing literature by investigating the direct effects of GHRM practices on employee environmental commitment in organizations. Published studies have focused on HRM practices that facilitate employee attitude and reactions (Nishii et al, 2008;Katou et al, 2014;Hitka, Kozubíková, & Potkány, 2018). In the green perspective, there few prior study explored this relationship (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, by using the Social exchange theory, this study provides a better understanding of GHRM application and it extends the existing literature by investigating the direct effects of GHRM practices on employee environmental commitment in organizations. Published studies have focused on HRM practices that facilitate employee attitude and reactions (Nishii et al, 2008;Katou et al, 2014;Hitka, Kozubíková, & Potkány, 2018). In the green perspective, there few prior study explored this relationship (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of educational policy was studied concerning the realities of social and political alienation and economic marginalization. Hitka et al, (2018) investigated the relationship between education and gender, based on the selected motivation factors. The results of the study confirmed the hypothesis that there are significant differences in the motivation factors among Slovak employees related to their gender and education.…”
Section: Social Capitalmentioning
confidence: 99%
“…Given the demographic situation, it is necessary to realise that the labour market in the upcoming years will be increasingly affected by the lack of replacement for retiring staff. The labour market will be influenced by factors such as changes in the preferences of students interested in studying at a university, different preferences in expectations of the quality of studies, lifestyle and goals, which influence their decisionmaking on the choice of future profession, as is confirmed by the research of Hitka et al (2018) or Freud (2006). The need for continuous education and the continuous development of competencies will continue to play a very important role in the life of every individual.…”
Section: Discussionmentioning
confidence: 99%